Predictors of Usage Intentions of Pirated Software - Phau, Ian (Journal of business ethics, 2010)
The purpose of this study is to investigate the salient factors influencing consumers’ attitudes and usage intentions towards pirated software. Using the Theory of Planned Behaviour, this study investigates the relationships between three sets of factors, i.e. personal, social and perceived behavioural control onto attitudes towards pirated software. Through a multiple regression, only personal factors have shown significant relationship with attitudes towards software piracy. Further results from this study have supported that favourable attitudes towards pirated software is likely to result in stronger intentions to use pirated software. It was found that computer proficiency acts as a predictor for intentions towards pirated software, rather than a moderator as originally postulated.